2008
DOI: 10.1007/s12355-008-0050-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimal rate of nitrogen for chewing sugarcane production in the southern Guinea Savanna of Nigeria

Abstract: Field trials were conducted to determine the optimal rate of nitrogen (N) for chewing sugarcane production in the Southern Guinea Savanna of Nigeria at the upland sugarcane experimental field of National Cereals Research Institute Badeggi (9°45'N, (06°7'E) in 1998 and 1999 wet seasons. In both the years 60kgN/ha resulted in significantly reduced lower growth parameters (germination percentage, tiller count, stalk length and yield tonne / ha). While among the four rates of 120, 180, 240 and 300kgN/ha there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Though this value is slightly greater than the ones obtained with other N rates, the difference is not significant. Gana (2008) established that for application of more than 120 kg N ha -1 , there was no significant difference between cane yields. For variety D 8484, cane yields averagely reached 127.1 TCH with application of 60 kg Nha -1 .…”
Section: Effects Of N Rates and Split Applications On Yield Of Co 421...mentioning
confidence: 97%
See 1 more Smart Citation
“…Though this value is slightly greater than the ones obtained with other N rates, the difference is not significant. Gana (2008) established that for application of more than 120 kg N ha -1 , there was no significant difference between cane yields. For variety D 8484, cane yields averagely reached 127.1 TCH with application of 60 kg Nha -1 .…”
Section: Effects Of N Rates and Split Applications On Yield Of Co 421...mentioning
confidence: 97%
“…A similar establishment was made by Thornburn et al (2001) who reported that cane yield was not affected with increasing N and Wiedenfeld (2000) who also depicted that rate of N application did not affect cane yields in the plant crop. Elsewhere, Rattey and Hogarth (2001) and Muchow et al (1995) reported that sugarcane quality reduced with increasing levels of N. Moreover, Gana (2008) established that for application of more than 120 kg N ha -1 , there was no significant difference between sugarcane yields. In a study carried out in Egypt, Ahmed et al (2009) showed that millable cane yields significantly responded to the used Nfertilizer levels.…”
Section: Introductionmentioning
confidence: 99%